THE IMPLEMENTATION OF INNOVATIVE LEARNING MODELS BASED ON 2013 CURRICULUM AT SMAN 5 JENEPONTO - Sulastri Syahrir (FKIP Unismuh Makassar, 2022)
The purpose of this study was to find out (1) the learning models implemented by English teachers and (2) how do the English teachers implemented of identified innovative learning models in teaching learning English at SMAN 5 Jeneponto. The subjects are 3 English teachers. The object of this research is implemented of five innovative learning models in teaching learning English. The instrument of this research is direct observation class to answer two objectives of this research.The findings of this research indicated that there were 3 innovative learning models implemented by English teachers, namely; Discovey learning, Problem-based learning, and Project-based learnin. The implementation of innovative learning models; (1) Discovey learning model, the steps are the teacher selection to the material, students to discovery and investigated of the problem, and self-analyzed the discovery data. (2) Problem-based learning, the teacher explained the material, students to find problem, students to presentation of the result, students provided reflection, and result of the investigation. (3) Project-based learning, the steps are students make a project related of material learning and solving of problem.